16‐1: Distinguished Student Paper: A Submillisecond‐response Liquid Crystal for Color Sequential Projection Displays. Issue 1 (May 2016) - Peng, Fenglin; Chen, Haiwei; Gou, Fangwang; Huang, Yuge; Wu, Shin‐Tson
Abstract : We report an LC mixture with low viscosity and high clearing point (Tc ∼102°C) for color‐sequential projection displays. Using a 1.95‐µm mixed‐mode twisted nematic (MTN) cell, the average gray‐to‐gray response time is less than 1ms, which is ∼3.6X faster than the current state of the art. Such an MTN LCoS can be used for near‐to‐eye wearable projection displays and headup displays in vehicles.